REPRESENTASI PERNIKAHAN DINI PERSPEKTIF: PRAMOEDYA ANANTA TOER - Wan Minto, Deri; Putriani, Ananda; Azwar, Rica; Indrayani, Teti; Ayunis (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The research was motivated by the phenomenon of early marriage which was criticized by Pramoedya Ananta Toer through a novel to the authorities "the elite at that time", so as not to carelessly marry women. Women who are married early certainly have an impact on psychology, thinking, and can trigger depression. This is in line with the phenomenon in 2022-2023 of many teenagers getting married in Indonesia without thinking about the lurking impact. The purpose of this study is to describe the representation of early marriage from Pramoedya Ananta Toer's perspective. Types of qualitative research with descriptive methods. Data in the form of sentences related to early marriage. Analysis techniques (1) describe data related to early marriage, (2) conduct data analysis, (3) conclude, (4) make research reports. Triangulation data validation techniques by means of internal and external validation. The results of the study, First, the cause of early marriage can be seen from the attitude of Beach Girl parents who want to get an ideal son-in-law who really hopes that their child's life is happy but their child ends up in misery Second, the impact of early marriage Beach Girl does not know anything, difficult to adapt to the environment and even always asks the importance of a marriage. In addition, the emotional state is unstable, readiness is immature, and less able to adapt to the social environment in society.